External incentives, social norms, and citizens’ participation in digital co‐production: A survey experiment - Jing Chen (Australian Journal of Public Administration, 2026)
Abstract With the rapid pace of digital transformation, motivating public participation has become a critical challenge for advancing both the theory and practice of digital co‐production. Drawing on incentive theory and social norm theory, this study uses a survey experiment conducted with Chinese citizens to explore their willingness to participate in digital co‐production, focusing on the effects of external incentives and social norms. The results show that material incentives are more effective than honour‐based incentives in driving participation. Additionally, positive descriptive norms have a stronger influence on participation willingness than negative norms. Notably, when positive descriptive norms are present, material incentives further amplify public engagement. This study offers insights into the motivational drivers behind citizen participation in digital co‐production and provides practical recommendations for governments on how to strategically leverage incentives and social norms to boost public involvement. Points for practitioners Material incentives appear to be more effective than honour‐based incentives in strengthening citizens’ willingness to participate in digital co‐production. Positive descriptive social norms demonstrate stronger effects than negative norms in promoting citizens’ willingness to engage in digital co‐production. The combination of material incentives and positive descriptive social norms may generate synergistic effects in enhancing citizens’ willingness to participate in digital co‐production.